Educação do campo no IFMT - Campus São Vicente : desafios da construção de uma educação dialógica - Senra, Ronaldo Eustáquio Feitoza (2014)
The debate on Rural Education in Brazil and in our state of Mato Grosso, is still a recent milestone, but lacking more discussions that can strengthen public policy. The objective of the research was to describe on the Rural Education to insertion into the Federal Institute of Science and Technology Mato Grosso, the campus IFMT Saint Vincent. Three dimensional spheres were considered as the scope of the research: (1) understanding the legal apparatus that constitute the field of education policy and how the reality of social movements is embodied in legislation; (2) the praxiological experience of training processes promoted the "Projovem field: knowledge and practices of the earth"; and (3) understanding of dialogical processes of rural social movements and the IFMT institution in critical perspective to interpret how the tensive dialogues were built between the instances that have their own separate policies. The thesis is guided through the case study of phenomenological nature and was to supply three instruments: (1) the literature on conceptual understanding, legal and documentary; (2) The case study to understand that fundamentally the phenomena that occurred in the educational experience of Projovem can not be replicated to other realities within the institution and not outside it; and (3) participatory research in the interpretation of policies that make up the itinerary of research, which form the axiological field of participation also the author of the thesis, as a subject involved in the process. The results show that the dialogic construction between different institutions is tensile, but occurs in an attempt to consolidate public policies in education field. Setting up current in discussions dating back to the counterculture of the 60s, field education is still a challenge to both the social movements as higher education institutions. However, there are still gaps of hopes and buildings full of possibilities for dialogue is still the desirable essence education.